Liturgical aspects of J. J. Overbeck's project of revival of the Orthodoxy of the Western rite - Alexey Chumichev (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
This article deals with an insuffi ciently studied topic in the history of interconfessional relations of the second half of the 19th century, namely the project of the revival of Western Orthodoxy, proposed by Julian Joseph Overbeck, the German theologian who lived in England. Overbeck can be rightfully regarded as a rather obscure and undeservedly forgotten fi gure. At diff erent times, Overbeck represented three Christian denominations: Catholicism, Protestantism, and thereafter Orthodoxy. Overbeck’s project was a unique phenomenon in the history of the Orthodox Church, because it was he who for the fi rst time put forward the idea of using the Western Rite as part of the Orthodox Church, which for many centuries after the Great Schism only practised the Oriental rite. In the 1870s, the plan proposed by Overbeck attracted unprecedented interest followed by support of the Holy Synod of the Russian Church. One of the main areas on which the Synodal Commission worked was the discussion of the rite of the Orthodox Mass (Liturgia Missae Orthodoxo-Catholicae Occidentalis) composed by him. This article addresses the liturgical aspect of Overbeck’s project and examines the work of the Synodal commission on the text of the Orthodox Mass as well as on some other liturgical traditions intended for use in Orthodox communities of the Western rite.